MORINGA OLEIFERA LEAF POWDER INFLUENCED THE CHEMICAL PROFILE OF LEONOTIS LEONURUS ESSENTIAL OILS. - Vambe, Mcmaster; Zengeni, Rebecca; Georgina Arthur; Singh, Karishma; Amoo, Stephen; Naidoo, Kuben; Coopoosamy, Roger. M. (Student’s Journal of Health Research Africa, 2024)
Background: Leonotis leonurus is used extensively in African herbal medicine to manage several diseases including diabetes mellitus, epilepsy, hypertension, and skin and respiratory infections. Although L. leonurusis a valuable medicinal plant in Africa, little has been done to improve the plant’s organoleptic and pharmacological properties. The study evaluated the effects of Moringa (Moringa oleifera) leaf powder treatments on the chemical profiles of essential oils from L. leonurus. Methodology: All trials were conducted in experimental greenhouse tunnels. Six-week-old L. Leonurus seedlings were transplanted into individual pots (1 seedling per pot) containing 1kg of GromorTM potting mix (30 dm3) and subjected to varying quantities (0, 1.25, 2.5, 5, 7.5, and 10g) of Moringa leaf powder (MLP) biweekly for eight weeks. Additionally, each seedling received 100 mL of 50 % Hoagland’s solution once every 4 weeks and was watered regularly throughout the trial. At the end of the trial, the plant’s shoots were harvested and essential oils were extracted from them by steam distillation. The oils’ chemical profiles were then determined by Gas Chromatography-Mass Spectroscopy. Results: MLP applications caused each treatment to have a distinct chemical profile. Notable variations in oil yield, number, and concentration of compounds per each sample evaluated were observed. Caryophyllene and humulene were among the bioactive compounds whose concentration increased by 4- to 10-fold in treatments, compared to the control. Caryophyllene, β-copaene, humulene, and phytol were among the most dominant compounds in the oil samples. Conclusions: MLP induced qualitative and quantitative changes in L. leonurus essential oils. The powder could therefore be potentially used to improve the quality and yield of medicinally valuable crucial oils from the plant. Recommendations: Future research could focus on maximizing the use of MLP in natural situations. Such field trials should also investigate the powder’s possible use in conjunction with other organic fertilizers.